THE VALUE OF STEWARDSHIP FOR THE MANAGEMENT OF BIRA BEACH AS TOURISM ATTRACTION - Ilham Junaid (Jurnal Kawistara, 2017)
Asean Economic Community (AEC) requires the tourism industry to employ human resources based on competencies as well as the necessary to manage tourism attraction (including beach) in sustainable ways. This research aims at proposing recommendation or strategies in managing Bira beach as tourism attraction under the framework of ‘stewardship’ for sustainable tourism. This research also investigates the visitors’ perception about the actual condition of Bira beach which then links to the value of stewardship. A qualitative research in 2015 (and updated in 2017) was employed to achieve the research goals through participant observation and interviews. The research reveals that in order to support Bira beach as tourism attraction, attention by different stakeholders is needed by implementing strategic management through the concept of stewardship. This paper recommends three kinds of stewardship including structural, functional and independent stewardships. The paper also argues that the stewardship concept is useful if there is high commitment and consensus among stakeholders to work based on the principles of responsibility.